If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 6 = 3x + 21 Reorder the terms: 6 + 6x = 3x + 21 Reorder the terms: 6 + 6x = 21 + 3x Solving 6 + 6x = 21 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6 + 6x + -3x = 21 + 3x + -3x Combine like terms: 6x + -3x = 3x 6 + 3x = 21 + 3x + -3x Combine like terms: 3x + -3x = 0 6 + 3x = 21 + 0 6 + 3x = 21 Add '-6' to each side of the equation. 6 + -6 + 3x = 21 + -6 Combine like terms: 6 + -6 = 0 0 + 3x = 21 + -6 3x = 21 + -6 Combine like terms: 21 + -6 = 15 3x = 15 Divide each side by '3'. x = 5 Simplifying x = 5
| 40x-3x^2=133.33333333 | | 3x+10=73-6x | | 9n^2-1=0 | | 5+12x=104+x | | 6=y-7 | | z+5=-16 | | 0.03x-(2x+3)=1.8 | | 56-3x=33x+16 | | 6c^2-72=11c | | 5b+6-2b=-12 | | -0.5+f=0.5 | | 6x+13=76-3x | | (X+4)(x-5)=9 | | -2x-x-5=13 | | -9=-17-n | | 5x+12=84-7x | | 120-3x=5x+8 | | x=6x-55 | | -5(2r+3)=3(11-4r)-58 | | 3x-4=12-103 | | -1+6x+7y=18y+24+6x | | -13-5x=5-7x | | 8a=4a+14 | | (3x-2)(3x-2)=16 | | 4x+21=14x-89 | | 5x^2-39x-8=0 | | 6x-11=2x+17 | | -100+3= | | f-(-11)=8 | | 5t-6=2t-24 | | -17-d=-8 | | e+(-14)=0 |